Amido-trihydroquinoline ligated rare-earth metal complexes for polymerization of isoprene. (12th April 2022) - Huo, Yanchen; Hu, Xiang; Wang, Jixing; Hu, Hongfan; Shi, Xiaochao
Abstract : In combination with a borate, the amido-trihydroquinoline ligated rare-earth metal complexes (Ln = Y, Lu) showed moderate catalytic activities for isoprene polymerization to generate 1, 4-enriched polyisoprenes. Abstract : Amido-trihydroquinoline ligated rare-earth metal complexes have been synthesized, and in combination with a borate, all these complexes (except 2-Sc ) showed moderate catalytic activities for isoprene polymerization to generate 1, 4-enriched polyisoprene. In particular, the 2-Y -based catalytic system promoted the isoprene polymerization in a well-controlled manner. The alkylaluminium (AlR3, R = Me, Et, i Bu) exerted a different influence on the polymerization, and AlMe3 enhanced not only the catalytic reactivity but also the 1, 4-selectivity significantly. Considering the influence of the polar sequence on improving the surface property of the non-polar polymer, we further successfully realized the polymerization of ε -caprolactone and its block copolymerization with isoprene by utilizing the active yttrium-polyisoprene species as the marcointiator. The fact that the higher content of the hydrophilic PCL sequence in the copolymer gave a lower WAC, proved the tunable modification of the copolymer's surface hydrophilicity.